Increased incidence and aetiological factors of back pain among Universiti Malaysia Sabah staff and undergraduates during the COVID-19 lockdown period - Rajesh Kumar Muniandy; D Kamarudin D Mudin; Yeap, Boon Tat; Voo, Peter Su Kiong (Malaysian Medical Association, 2022)
Introduction: In response to the coronavirus disease 2019 (COVID-19) pandemic, many countries have introduced work from home campaigns. Most teaching faculties have moved to an online delivery mode, which could put students and teachers at risk of back pain. The aim of this study was to determine the frequency of newly diagnosed back pain among lecturers and undergraduates from a tertiary education centre during the COVID-19 lockdown and to identify the possible factors associated with this back pain. Materials and Methods: This study was a cross-sectional survey conducted among 1,500 lecturers and students of Universiti Malaysia Sabah (UMS). The questionnaire used was modified from previous studies on back pain. Results: There were 346 newly diagnosed cases of back pain among students and lecturers of UMS. More than half of the participants (61.2%) suffered lower back pain in the lumbar region. There was a significant correlation between increased time of sitting and reduced exercise time, and the incidence of back pain. Poor ergonomic sitting conditions and poor perceived health conditions during the lockdown period also had a significant impact on the frequency of back pain. Conclusion: The university community has undergone a significant increase in sitting time and a decrease in exercise time during the lockdown. This has contributed to an increase in the frequency of back pain. It is recommended that further studies be done to guide the university community regarding the maintenance of exercise and management of sitting hours, in order to reduce the frequency of back pain.